Improving Students’ Creative Thinking Skills Assisted by GeoGebra Software - Al Ayyubi, Ibnu Imam; Rohmatulloh, Rifqi; Suryana, Irfan; Wijaya, Tommy Tanu (Noumerico: Journal of Technology in Mathematics Education, 2024)
This study aims to improve students’ creative thinking skills in problem-based, ill-structured, open-ended learning through stimulus. This study used learning strategies that simultaneously develop problem-solving strategies and knowledge discipline. This learning can be achieved if educational activities are focused on authentic, contextual, and relevant tasks or problems so that students can gather the necessary information, evaluate alternative solutions, and present solutions they believe in. Moreover, the ability to generate uncommon or extraordinary ideas must be raised from the problems that exist in learning. The ability to think creatively in mathematics in education using the Problem-Based Learning (PBL) approach assisted by GeoGebra is expected to be a practical approach to educating students in increasing their intellectual potential and familiarizing them to deal with non-routine problems and applying it in their daily life to become a student who can think creatively. This study used a quasi-experimental research method with a quantitative approach conducted at SMA Negeri 2 Cimalaka. The instruments used in this study were questionnaires and tests. This study's approach, which was integrated with GeoGebra, can be used as an alternative to learning mathematics in schools. It can be developed with other approaches according to problems in mathematics.